Mathematical Thinking Styles and Its Implications in Science Learning: A Bibliometric Analysis - Erpin Evendi (Postgraduate, University of Mataram, 2022)
Mathematical thinking style is an aspect that needs to be studied, especially its implications for the practice of science pedagogy in the classroom, considering the role of mathematics in science learning is very important. Studies related to this theme are seen as very interesting and also very relevant to support future teaching and research practices. The purpose of this study is to conduct a bibliometric analysis of mathematical thinking styles and their implications in science learning. Specifically, this bibliometric study aims to describe and examine literature in areas that are coherent with the concept of mathematical thinking style, and coherence between mathematical thinking style and science learning. The SCOPUS database is used as a source of document information. Screening and document analysis were carried out according to the keywords inserted in the 'search document' menu. With several modes of screening documents in areas that are coherent with the concept of mathematical thinking style and its implications in science learning, a number of documents were found that examine the subject area. The specific screening steps and document findings are discussed further in this article. Basically, specific articles that are coherent with the theme of bibliometric analysis 'mathematical thinking styles and their implications in learning science' describe the importance of studies related to students' mathematical thinking styles. Differences in students' thinking styles become a big challenge for teachers' pedagogical practices in teaching mathematics and science. This is an important implication in this study, and teachers must find the best way to conduct mathematics and science learning in the light of the different mathematical thinking styles of students. Finally, this study can be a reference in future studies that will explore themes related to mathematical thinking styles